2020
DOI: 10.1021/jacs.0c11437
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Dependent DNA Base Pairing of 5-Carboxyuracil with Itself and All Four Canonical Nucleobases

Abstract: A 5-carboxyuracil (caU) nucleobase was found to pair not only with A (caU–A) by hydrogen bonding but also with other DNA nucleobases by metal coordination bonding. Metal-dependent formation of caU–CuII–caU, caU–HgII–T, caU–AgI–C, and caU–CuII–G pairs was demonstrated by duplex melting analysis and mass spectrometry. The duplexes containing caU–X (X = caU, T, C, and G) were significantly stabilized in the presence of the corresponding metal ions, while the DNA duplexes containing the caU–A pairs were destabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…A variety of ligand-type articial nucleobases have been developed so far by modifying simple ligand scaffolds such as pyridine, [38][39][40] maltol 41,42 and pyrimidine. [43][44][45][46][47][48] Among them, the imidazole ligand is one of the smallest scaffolds. It has been reported that most of the modied imidazole nucleobases form Ag I -mediated base pairs by N-Ag I -N coordination.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of ligand-type articial nucleobases have been developed so far by modifying simple ligand scaffolds such as pyridine, [38][39][40] maltol 41,42 and pyrimidine. [43][44][45][46][47][48] Among them, the imidazole ligand is one of the smallest scaffolds. It has been reported that most of the modied imidazole nucleobases form Ag I -mediated base pairs by N-Ag I -N coordination.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These metal base pairs have advanced as promising candidates for a number of applications including the development of nanomolecular devices, 5 ion sensors and biosensing devices 6,7 and metal nanowires and nanodevices [8][9][10] as well as for the allosteric control of functional nucleic acids. [11][12][13][14] The formation of metal base pairs mainly occurs by annealing short synthetic oligonucleotides together with specific metal cations. While this approach has allowed the identification of metal base pairs based on natural and modified nucleotides, it is restricted in oligonucleotide size and in terms of diversity of functional groups that can be explored due to the rather harsh conditions imposed by solid-phase synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These metal base pairs have advanced as promising candidates for a number of applications including the development of nanomolecular devices, 5 ion sensors and biosensing devices 6,7 and metal nanowires and nanodevices 8–10 as well as for the allosteric control of functional nucleic acids. 11–14…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These metal base pairs have advanced as promising candidates for a number of applications including the development of nanomolecular devices, 5 ion sensors and biosensing devices 6,7 and metal nanowires and nanodevices [8][9][10] as well as for the allosteric control of functional nucleic acids. [11][12][13][14] The formation of metal base pairs mainly occurs by annealing short synthetic oligonucleotides together with specific metal cations. While this approach has allowed the identification of numerous metal base pairs, it is restricted in oligonucleotide size and in terms of diversity of functional groups that can be explored due to the rather harsh conditions imposed by solidphase synthesis.…”
Section: Introductionmentioning
confidence: 99%